Prediction of trajectory and fate of the Nissos Amorgos oil spill - Rincón, José; Reyes, Miguel; Viada, Sandra (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper presents the trajectory modeling results of the oil spill occurred in the Gulf of Venezuela as result of the hull damage of the tanker Nissos Amorgos. The computational code “DROG3D” developed at North Carolina University (USA) was used to described drogue trajectory, under the influence of the tidal currents. The local tidal and current information was obtained from another Finite Element based code which solves the shallow water equations. The prediction of the oil slick trajectory and its visual reports are in good agreement and the final oil location was spotted within the zone indicated by the model.